Phytochemistry and GCMS Analysis of Ethanol and Aqueous Stembark Extracts of Detarium microcarpum Guill. & Perr. Fabaceae - Dahiru, Mubarak Muhammad; Musa, Neksumi; Badgal, Enoch Buba (Sciences of Phytochemistry, 2025)
The therapeutic applications of medicinal plants in the treatment of various diseases can be attributed to their diverse phytochemical constituents. This study aimed to investigate the phytochemical composition of aqueous and ethanol stem bark extracts of Detarium microcarpum. Qualitative and quantitative analyses were conducted to determine the presence and concentrations of phytochemicals, followed by the identification of phytoconstituents using gas chromatography-mass spectrometry (GC-MS). The aqueous extract was found to contain saponins (27.11 ± 0.22%) and flavonoids (47.33 ± 0.70% ), with alkaloids, steroids, glycosides, and terpenoids absent. In contrast, the ethanol extract contained alkaloids (10.78 ± 0.59%), saponins (45.11 ± 0.48%), glycosides (5.44 ± 0.48%), and flavonoids (11.00 ± 0.77%), while steroids and terpenoids were not detected. GC-MS analysis revealed 14 compounds in the aqueous extract and 20 in the ethanol extract. The major constituents of the aqueous extract included hydroperoxide, 1,4-dioxan-2-yl (58.32%), 1,2,3-benzenetriol (16.44%), and cis-p-coumaric acid (11.05%). In the ethanol extract, the predominant compounds were coumarin (29.41%), benzofuran (17.23%), and catechol (9.23%). The identified compounds may serve as potential synthetic templates for the development of novel therapeutic agents targeting various diseases. This study supports the ethnomedicinal use of D. microcarpum and provides a scientific basis for its role in traditional medical practices.